Development of guided inquiry-oriented e-worksheets to improve students' science process skills in acid-base material - Dini Catur Anisah; Harun Nasrudin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to describe the feasibility of guided inquiry-oriented E-worksheets to improve students' science process skills on acid-base material. The research method is Research and Development (R&D), using the 4D development model, which is limited to the development stage and limited trials on 38 eleventh grades at Al-Islam Krian senior high school. The results showed the feasibility of E-worksheets as follows : (1) The validity of E-worksheets based on the criteria of content, presentation, language, and graphics, obtained the mode in E-worksheets 1 and E-worksheets 2, respectively: content criteria 5 and 5; presentation criteria 4.5 and 4.5; language criteria 4 and 4; graphic criteria 5 and 5 with valid and very valid categories, so that the developed E-worksheets are feasible based on the validity criteria. (2) The practicality of the E-worksheets is reviewed from the responses and activities of students. Learner responses based on content, presentation, language, and graphic criteria obtained a percentage of 96.42%; 96.70%; 99.12%; and 100% with a very practical category. Relevant learner activities at meeting 1 and meeting 2 received a percentage of 95.02% and 96.56% in the very practical category. (3) E-worksheets' effectiveness is based on improving science process skills. A normality test showed a significant score on the pretest and posttest of 0.004 and 0.000, respectively, so the significance < 0.05 showed that its data was not distributed normally. Furthermore, pretest and posttest data are analyzed using the Wilcoxon signed rank test, with a significance score of 0.000 < 0.05, showing a significant difference in pretest and posttest results. Data pretest and posttest then also analyze using N-gain with a score from 0.70 to 1.00 with a high category, so students' science process skills are said to increase. E-worksheets effectively improve science process skills.